Plasma pentadecanoic acid is modestly related to cardiovascular health in CARDIA and ARIC cohorts: observational associations without evidence of causality - Steffen, Brian T.; Jacobs, David R.; Li, Aixin; Tang, Weihong; Duprez, Daniel; Mathew, Mahesh; Lutsey, Pamela L.; Yi, So-Yun; Zhou, Xia; Steffen, Lyn M. (Frontiers in Nutrition, 2026)
BackgroundPentadecanoic acid (C15:0) is an odd-chain saturated fatty acid that is being marketed as a heart-healthy supplement.ObjectiveTo test whether plasma C15:0 is related to cardiovascular outcomes including systolic and diastolic blood pressure (SBP and DBP), functional cardiac measures, and development of hypertension and cardiovascular disease (CVD).MethodsPlasma phospholipid C15:0 levels were assessed by gas chromatography in 3,196 Coronary Artery Risk Development in Young Adults participants (mean age 45 years; 57% female; 45% Black). Generalized linear models estimated associations of plasma C15:0 with SBP, DBP, and echocardiographic indices. Cox regression estimated risk of incident hypertension (SBP/DBP ≥ 140/90 mmHg or BP medication use) or CVD over a median 10-year period. Covariate adjustments were included to control for likely confounders. Significant associations were tested in a replication subcohort of 3,889 White participants of the Atherosclerosis Risk in Communities Study (ARIC) (mean age 54 years; 52% female) using comparable methods. Two-sample Mendelian randomization (MR) tested for potential causality.ResultsHigher plasma C15:0 levels (per SD) were associated with lower SBP (mm Hg) [β = −1.47 (95% CI, −1.99, −0.96)], DBP (mm Hg) [β = −1.13 (95% CI, −1.51, −0.74)], and 10-year risk of incident hypertension [hazard ratio = 0.86 (95% CI, 0.78, 0.95)]. These associations were replicated in the ARIC sample. C15:0 levels were not associated with incident CVD in either cohort or with echocardiographic parameters in CARDIA. Two-sample MR analyses provided no evidence for a causal effect of C15:0 on SBP, DBP, resting heart rate, or hypertension.ConclusionObservational associations between plasma C15:0 and cardiovascular risk markers were modest but were not supported by cardiac function or MR findings. The collective evidence is not consistent with a causal cardiovascular benefit of C15:0.